دور العوامل الاجتماعية والوظيفية في الحلول المعاصرة للسكن الباثيوي - قنصلية, جورج (Latakia University Journal -Engineering Sciences Series, 2019)
ترتبط درجة تحقيق البناء السكني للاحتياجات والمتطلبات الوظيفية والاجتماعية لسكانه ارتباطاً وثيقاً بمستوى الكفاءة العامة للحل المعماري, فقد أظهرت الدراسات المعاصرة اهتماماً كبيراً بمعالجة هذه الجوانب في حلول البناء السكني من خلال اقتراح نماذج سكنية متنوعة استندت في بعض خصائصها إلى المسكن التقليدي مستفيدة من كثير من المزايا الاجتماعية والوظيفية لهذا المسكن، وذلك في إطار السعي الدائم لتطوير هذه المزايا والخصائص بما يتلاءم مع المتطلبات العصرية. يعمل البحث على تحديد المتطلبات والاحتياجات الوظيفية والاجتماعية للبناء السكني من خلال استقراء أداء نماذج البناء السكني المختلفة في هذا المجال, ثم يقوم البحث باعتماد هذه المتطلبات، والاحتياجات بوصفها معايير تقييمية في الدراسة التحليلية لنماذج مختلفة من حلول السكن الباثيوي المعاصر. تظهر الدراسة تمتع حلول السكن الباثيوي بمزايا وخصائص هامة تمكنها من تحقيق مستوى مرتفع من الأداء الوظيفي كما تمكنها من توفير جملة كبيرة من الاحتياجات والمتطلبات الاجتماعية. تعرضت الدراسة أيضاً للجوانب السلبية لهذه الحلول والتي تبين بالنتيجة أنها محدودة جداً كما أن البعض منها ينطبق فقط على بيئة اجتماعية محددة. The degree of constructing houses that meet the needs and functional and social requirements of inhabitants is closely connected to the level of general efficiency of the architectural solution. Recent studies have shown a great interest in treating these aspects of building solutions through suggesting various housing models. In some of their specification, these models were based on the traditional abode, making use of many of its social and functional specifications in an attempt to develop these specifications to meet modern requirements. This paper attempts to determine the social and functional requirements of an abode through analytical studies of the functioning of different housing models. After adopting these points as evaluation standards for the home model, this paper makes an analytical study of different models of modern courtyard houses according to these standards. This study shows that solutions to courtyard houses displaying important specifications enable them to achieve a high level of functional performance and provide a lot of social needs. This study has also dealt with the negative aspects of these solutions, which show that they are too limited, since some of them apply only to a specific social environment.